Circular motion Unruh effect: in spacetime and in the laboratory - Bunney, Cameron Richard David (2024)
Quantum Field Theory in Curved Spacetime (QFTCS) is an approximation to the union of General Relativity (GR) and Quantum Field Theory (QFT). Born out of Parker's investigations into cosmological particle creation, QFTCS has since flourished into a productive field in its own right, giving rise to predictions such as black-hole evaporation and the Unruh effect, which states that a uniformly linearly accelerated observer will react to the Minkowski vacuum as if it were a thermal state in temperature T=ℏa/(2πck). Later, in 1981, Unruh demonstrated that acoustic perturbations in a fluid may equivalently be described as a scalar field propagating on a curved spacetime, whose geometry is characterised by the background fluid flow. Furthermore, Unruh found that "the same arguments which lead to black-hole evaporation also predict a thermal spectrum of sound waves should be given out from the sonic horizon in transsonic fluid flow." With this discovery, analogue gravity was born. Over the past forty years, several analogue-gravity and early-Universe simulators have been devised, using physical systems such as ultracold atoms, optical devices, and fluid interfaces. Motivated by the inherent temperature and finite size of the spacetimes provided by these analogue systems, this Thesis extends the theoretical modelling of an accelerated observer to include the effect of thermality and spatial confinement.